2020
DOI: 10.1021/acs.nanolett.0c00125
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Dispersion of Room-Temperature Exciton-Polaritons with Perovskite-Based Subwavelength Metasurfaces

Abstract: Exciton-polaritons, elementary excitations arising from the strong coupling regime between photons and excitons in insulators or semiconductors, represent a promising platform for studying quantum fluids of light and realizing prospective all-optical devices. Among different materials for room temperature polaritonic devices, twodimensional (2D) layered perovskites have recently emerged as one of the promising candidates thanks to their prominent excitonic features at room temperature. Here we report on the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 63 publications
3
50
0
Order By: Relevance
“…Beside the electrical properties of the metal film, we will exploit its surface plasmons coupled with excitons of the perovskite to realize the formation of exciton-surface plasmon polaritons which have also been observed in several works [6,41]. Lately, it has been demonstrated that perovskite-based metasurface of subwavelength periodic lattice offers an on-demand energy-momentum polaritonic dispersion [47]. While this work only discussed on the real part (i.e.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Beside the electrical properties of the metal film, we will exploit its surface plasmons coupled with excitons of the perovskite to realize the formation of exciton-surface plasmon polaritons which have also been observed in several works [6,41]. Lately, it has been demonstrated that perovskite-based metasurface of subwavelength periodic lattice offers an on-demand energy-momentum polaritonic dispersion [47]. While this work only discussed on the real part (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…To model the perovskite material, we use the dielectric function of phenethylammonium lead [27,31,37,42,47]. In this model, the excitonic resonance is described by a Lorentz oscillator, with dielectric function given by [54]:…”
Section: Surface Plasmon Polariton (Spp) and Dielectric Guided Mode (Dgm) Of Perovskite Thin Film On Metallic Substratementioning
confidence: 99%
See 2 more Smart Citations
“…[ 7 ] A broad spectrum of active layers is currently being investigated among inorganic semiconductors (such as GaN, [ 8 ] ZnO, [ 9 ] and perovskites [ 10,11 ] ), organic semiconductors, and hybrid materials. [ 12–15 ] Organic semiconductors contain localized Frenkel excitons with high exciton binding energy (of several hundreds of meV) and high oscillator strength. These attractive properties enable demonstration of strong coupling at room temperature.…”
Section: Introductionmentioning
confidence: 99%